2004
DOI: 10.1124/mol.65.3.639
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole Alters Cardiac Substrate Preference by Inducing Translocation of FAT/CD36, but Not That of GLUT4

Abstract: In cardiac myocytes, uptake rates of glucose and long-chain fatty acids (FA) are regulated by translocation of GLUT4 and FA translocase (FAT)/CD36, respectively, from intracellular stores to the sarcolemma. Insulin and contractions are two major physiological stimuli able to induce translocation of both transporters and therefore enhance the uptake of both substrates. Interestingly, the cardiovascular drug dipyridamole was able to enhance FA uptake but had no effect on glucose uptake. The selective stimulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…Our results show that lowintensity muscle contraction increased both glucose and FA uptake without significantly increasing AMPK activity, providing evidence that AMPK activation may not always be necessary to measure contraction-induced increases in FA and glucose uptake. In agreement with other data (8,15,17), our results suggest that AMPK-independent mechanisms may be involved in the regulation of contraction-induced FA and glucose uptake under some conditions. Indeed, in quiescent rat cardiac myocytes, dipyridamole, an inhibitor of nucleoside transport, was shown to induce FAT/CD36 translocation and FA uptake without stimulating AMPK activity (17).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results show that lowintensity muscle contraction increased both glucose and FA uptake without significantly increasing AMPK activity, providing evidence that AMPK activation may not always be necessary to measure contraction-induced increases in FA and glucose uptake. In agreement with other data (8,15,17), our results suggest that AMPK-independent mechanisms may be involved in the regulation of contraction-induced FA and glucose uptake under some conditions. Indeed, in quiescent rat cardiac myocytes, dipyridamole, an inhibitor of nucleoside transport, was shown to induce FAT/CD36 translocation and FA uptake without stimulating AMPK activity (17).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other data (8,15,17), our results suggest that AMPK-independent mechanisms may be involved in the regulation of contraction-induced FA and glucose uptake under some conditions. Indeed, in quiescent rat cardiac myocytes, dipyridamole, an inhibitor of nucleoside transport, was shown to induce FAT/CD36 translocation and FA uptake without stimulating AMPK activity (17). In slow oxidative muscle it has been shown that, although a high precontraction glycogen level prevented the contraction-induced activation of AMPK, it did not reduce the rate of contraction-induced glucose uptake (8).…”
Section: Discussionsupporting
confidence: 93%
“…Recent work in our group and by others has shown that insulin and leptin, as well as the pharmacological agents oligomycin, AICAR, and dipyridamole, induce the translocation of CD36 in skeletal muscle (164,278,305) and heart (73,153,274,281,305,324). Insulin has also been reported to induce FATP1 translocation in adipocytes (399), but this insulin-induced FATP1 translocation in adipocytes was not observed in another study (346), or in the heart (73,152).…”
Section: Endocrine-mediated and Pharmacologically Induced Regulation mentioning
confidence: 89%
“…However, recently we have identified pharmacological compounds able to selectively recruit either transporter thereby increasing the rate of uptake of a single type of substrate. The phosphodiesterase inhibitor dipyridamole was found to mobilize CD36 from contraction-inducible storage depots while not affecting GLUT4 mobilization [18]. This stimulatory action of dipyridamole-which is unrelated to its effects on phosphodiesterase inhibition and on nucleoside transport, but likely due to activation of a yet unidentified protein kinase which is situated in the contraction signaling cascade downstream of AMPK-was accompanied by a higher rate of LCFA uptake and a decreased glucose uptake.…”
Section: Signaling and Trafficking Pathways Involved In Mobilization mentioning
confidence: 92%